Analisis Risiko Audit dan Strategi Mitigasinya dalam Menghadapi Perubahan Lingkungan Bisnis pada Sektor Perbankan - Annisa Fitriah Mudassir (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Changes in the business environment of the banking sector during the 2020–2025 period have created new challenges for audit activities. The COVID-19 pandemic, accelerated digital transformation, the development of financial technology (fintech), cybersecurity threats, and regulatory changes have significantly altered the banking risk profile. These conditions require auditors to adopt a more adaptive Risk-Based Auditing (RBA) approach in identifying, assessing, and managing risks. This study aims to analyze the impact of changes in the business environment on audit risk, identify the challenges faced by auditors, and formulate effective mitigation strategies in the banking sector. The study employs a qualitative approach using a synthetic case study method based on secondary data derived from banks’ annual reports, regulatory publications, industry reports, and academic literature from 2020–2025. The findings indicate that changes in the business environment have increased the complexity of audit risks, particularly those related to technology-based operational risks, compliance risks, strategic risks, and cybersecurity risks. The main challenges faced by auditors include the increasing velocity of risk changes, gaps in information technology competencies, the complexity of digital data management, and the limitations of conventional audit methods. Therefore, the utilization of audit technology, enhancement of auditor competencies, integration of audit and risk management functions, and the implementation of continuous auditing are essential strategies for improving the effectiveness of Risk-Based Auditing.